Techno-environmental assessment of a hydrogen-fuelled combined-cycle gas turbine for a liquid hydrogen tanker - Alkhaledi, Abdullah N. F. N. R.; Batra, Amit; Sampath, Suresh; Pilidis, Pericles (Elsevier, 2022)
The purpose of this study was a techno-environmental assessment analysis for a 280,000 m3 liquid hydrogen (LH2) tanker powered by a hydrogen-fuelled combined-cycle gas turbine (COGAS) as the prime mover. This study utilised established and reliable methods to simulate the LH2 tanker in different journeys and conditions for analysing the advantages of the hydrogen-fuelled COGAS in terms of performance and emission reduction. The assessment was based on engine behaviour on different journeys under cargo loaded and unloaded conditions, with a normal and a 6% degraded engine, and under various ambient conditions. According to the results, the single-pressure hydrogen-fuelled COGAS reached a maximum overall thermal efficiency of 55.5% in winter under unloaded and normal engine conditions at a ship speed of 18 knots during the journey from Marseille to Algeria. From an environmental perspective, the maximum NOx emission of the COGAS was 3.5 kg/h during the journey from Tangier to Southampton in summer with a 6% degraded engine under the loaded condition at a ship speed of 18 knots. The results of the techno-environmental assessment indicated that the LH2 tanker powered by the hydrogen-fuelled COGAS could successfully achieve high efficiency and low emission targets in off-design conditions. The outcome of this study will lead to a future investigation of the LH2 tankers operation economic aspects.
Keywords: Liquid hydrogen tanker; Engine thermal efficiency; Combined-cycle gas turbine; NOx emissions; Hydrogen-fuelled engine; LH2 tanker mission